Implementación de un sistema acuapónico hibrido (solar y tradicional) para el cultivo de tilapia roja, especies seleccionadas y forraje verde hidropónico como estrategia de producción más limpia en Polo Nuevo, Atlántico (2022)
The department of Atlántico, Colombia contemplates in its economic activities agriculture and fish farming, sectors that are currently affected by different factors including the phenomenon of El Niño and La Niña, which prevent a lasting harvest to farmers, under this problem arose the need to implement a hybrid aquaponic system in order to ensure food security in the municipality of Polo Nuevo Atlántico, to achieve this it was necessary to consult the needs and technical requirements that contemplates the development of a successful aquaponic system. An irrigation evaluation was carried out to detect and minimize the hazards that could occur in the cultivation and hydroponics. The pilot tests showed expected results such as compliance with the weight and length estimates of the fish biometrics, and the cattle on the farm accepted the hydroponic Green fodder as food. During the development of the project, it was verified that every execution or activity complied with the cleaner production guidelines.